2018
DOI: 10.1007/s11136-018-1803-x
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS depression measures perform similarly to legacy measures relative to a structured diagnostic interview for depression in cancer patients

Abstract: The convergent and criterion validity of the PROMIS depression measures in cancer populations was confirmed, although the optimal cut-off points are not established. PROMIS measures were briefer than BDI-II and CES-D but do not offer any advance in terms of diagnostic accuracy, reduced response burden or cost over other legacy measures of depression in oncology patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 25 publications
4
51
0
Order By: Relevance
“…By examining concordance of the PROMIS‐D‐SF with a structured diagnostic interview, the results of the current study have provided novel information to guide its application in this population at risk of depression. Consistent with previous studies, we found overall good concordance between the PROMIS‐D‐SF and the SCID, but when we evaluated the PROMIS‐D‐SF as a screening instrument for individual YACS, the results were not robust. All PROMIS‐D‐SF cutoff t‐scores fell short of our minimum criteria for both high sensitivity (≥85%) and moderate specificity (≥75%), and the results indicated that screening YACS using the PROMIS‐D‐SF would lead both to a significant percentage of symptomatic survivors being missed and a significant percentage of clinical referrals being deemed unnecessary according to SCID criteria.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…By examining concordance of the PROMIS‐D‐SF with a structured diagnostic interview, the results of the current study have provided novel information to guide its application in this population at risk of depression. Consistent with previous studies, we found overall good concordance between the PROMIS‐D‐SF and the SCID, but when we evaluated the PROMIS‐D‐SF as a screening instrument for individual YACS, the results were not robust. All PROMIS‐D‐SF cutoff t‐scores fell short of our minimum criteria for both high sensitivity (≥85%) and moderate specificity (≥75%), and the results indicated that screening YACS using the PROMIS‐D‐SF would lead both to a significant percentage of symptomatic survivors being missed and a significant percentage of clinical referrals being deemed unnecessary according to SCID criteria.…”
Section: Discussionsupporting
confidence: 85%
“…Although studies previously have evaluated the PROMIS‐D‐SF as a screening instrument in cancer and other medical populations, we are not aware of any such study conducted with YACS. By examining concordance of the PROMIS‐D‐SF with a structured diagnostic interview, the results of the current study have provided novel information to guide its application in this population at risk of depression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations